Membranes: Materials and Fractal Designs for 3D Multifunctional Integumentary Membranes with Capabilities in Cardiac Electrotherapy (Adv. Mater. 10/2015). (March 2015) - Xu, Lizhi; Gutbrod, Sarah R.; Ma, Yinji; Petrossians, Artin; Liu, Yuhao; Webb, R. Chad; Fan, Jonathan A.; Yang, Zijian; Xu, Renxiao; Whalen, John J.; Weiland, James D.; Huang, Yonggang; et al.
<x xml:space="preserve">Abstract</x> An optical image of a 3D multifunctional integumentary membrane integrated on a Langendorff‐perfused rabbit heart is shown. The inset shows an epicardial electrogram recorded using integrated fractal electrodes with PEDOT:PSS coatings, as described by J. A. Rogers and co‐workers on page 1731. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>